2018
DOI: 10.1002/ldr.2920
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and AMPA concentrations in wind‐blown material under field conditions

Abstract: Agricultural intensification in fragile arid and semiarid environments has led to an increase in soil degradation, mainly through wind erosion. Argentina is an agricultural and cattle‐farming country, which has increased its productivity in the last few decades, widening the boundaries of farm land and the use of herbicides to control weeds. Glyphosate, which accounts for 65% of the Argentinian pesticides market, is strongly retained in soil. The World Health Organization concluded that there was evidence to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
1
16
0
4
Order By: Relevance
“…Additionally, during the second and third sampling year a larger area of wheat was sown: the increase was greater than 100% between the first season and the next two. This crop implies a lower use of herbicides than winter fallow and reduces the environmental movement of pesticides by reducing erosion since it generates coverage in the season of stronger winds and decreases wind erosion, which is responsible for displacing soil particles enriched with glyphosate and AMPA [32]. Finally, due to the emergence of resistant weeds and spot spray systems, there is a downward trend of applied doses although the number of applications per year remains constant.…”
Section: Glyphosate and Its Metabolite Ampamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, during the second and third sampling year a larger area of wheat was sown: the increase was greater than 100% between the first season and the next two. This crop implies a lower use of herbicides than winter fallow and reduces the environmental movement of pesticides by reducing erosion since it generates coverage in the season of stronger winds and decreases wind erosion, which is responsible for displacing soil particles enriched with glyphosate and AMPA [32]. Finally, due to the emergence of resistant weeds and spot spray systems, there is a downward trend of applied doses although the number of applications per year remains constant.…”
Section: Glyphosate and Its Metabolite Ampamentioning
confidence: 99%
“…In semiarid areas, wind erosion plays an important role since the risk of transporting glyphosate and AMPA with suspended dust is very high and they hardly decompose under dry soil conditions [38]. Aparicio et al [32] analyzed sediments collected in the province of Chaco, Argentina, and found 0.66-313 µg kg −1 of glyphosate and 1.3-83 µg kg −1 of AMPA, confirming that wind-eroded material can contribute to water pollution. Furthermore, glyphosate reaching the atmosphere through drift or wind erosion can be washed away by rain.…”
Section: Glyphosate and Its Metabolite Ampamentioning
confidence: 99%
“…Glyphosate and AMPA are frequently reported to occur in surface water (Okada et al, 2018;Primost et al, 2017;Jayasumana et al, 2015;Battaglin et al, 2014;Aparicio et al, 2013;Hanke et al, 2010;Battaglin et al, 2009;Botta et al, 2009;Struger et al, 2008;Scribner et al, 2007;Kolpin et al, 2006;Battaglin et al, 2005;Humphries et al, 2005;Scribner et al, 2003), streambed sediment (Primost et al, 2017;Battaglin et al, 2014;Aparicio et al, 2013;Peruzzo et al, 2008) and suspended matter (Okada et al, 2018;Primost et al, 2017;Aparicio et al, 2013). Despite their low potential for leaching and low volatility, they have also been reported to occur in groundwater (Okada et al, 2018;Jayasumana et al, 2015;Battaglin et al, 2014;van Stempvoort et al, 2014;Sanchís et al, 2012;Scribner et al, 2007;Brüsch, 2006), rainwater (Battaglin et al, 2014;Chang et al, 2011;Scribner et al, 2007;Humphries et al, 2005;Quaghebeur et al, 2004) and atmospheric dust (Aparicio et al, 2018;Chang et al, 2011;Humphries et al, 2005).…”
Section: Off-site Transport Pathwaysmentioning
confidence: 99%
“…Although the atmospheric transport of glyphosate and AMPA associated to the particle phase seems extremely likely, studies focusing on their transport with wind erosion are lacking. In fact, just very recently one study was published on the transport of glyphosate and AMPA with wind-blown material under field conditions, indicating high concentrations of these compounds in the dust of agricultural regions of Argentina (Aparicio et al, 2018).…”
Section: Off-site Transport Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation